Halal Tourism Ecosystem In Indonesia - uslan, sugianto; Mutmainah, Siti (Al-Hijrah: Journal of Islamic Economics And Banking, 2025)
Tourism is a sector with great potential to be developed in various countries. Indonesia has the opportunity to develop halal tourism because 86.7% of the population is Muslim. In the last two years, Indonesia's ranking in the Global Muslim Travel Index (GMTI) has increased rapidly. In 2023, Indonesia won the title of Top Muslim Friendly Destination of the Year at the GMTI event in Singapore. This research will discuss the Halal Tourism Ecosystem in Indonesia, focusing on the formulation of the halal tourism ecosystem in Indonesia, the halal value chain of the halal tourism industry, the potential for developing halal tourism in Indonesia. This research uses a qualitative approach with descriptive methods. Data were obtained through a review of various literatures, and analyzed using a content analysis approach on themes relevant to the halal tourism ecosystem in Indonesia. The findings of this study: first, Indonesia's halal tourism ecosystem is formed from the culinary, lodging, service, and Islamic finance sectors with government support. A large market and sharia facilities encourage Indonesia to become the best halal tourism destination GMTI 2023. Second, the halal tourism value chain includes destinations, transportation, accommodation, culinary, and travel and tour services. Third, halal tourism in Indonesia is very potential because the majority of the population is Muslim and strong government support. Indonesia is also recognized worldwide as the best halal tourist destination according to GMTI 2023.